To fully simplify the expression x^2y^3(16x^3y^4), we can use the rules of exponents and simplify the expression step by step:
First, we can multiply the coefficients in the expression:
16 * 1 = 16
Next, we can multiply the x terms together by adding their exponents:
x^2 * x^3 = x^(2+3) = x^5
Then, we can multiply the y terms together by adding their exponents:
y^3 * y^4 = y^(3+4) = y^7
Putting it all together, the fully simplified expression is:
16x^5y^7
fully simplify
x^2y^3(16x^3y^4)
1 answer